Second Language Acquisition and Mother Tongue Influence of English Language Learners – A Psycho Analytic Approach - Delbio, A.; Abilasha, R.; Ilankumaran, m. (International Journal of Engineering and Technology, 2018)
Language is a tool used to convey oneâ€™s thoughts, feelings and needs. Mother tongue is the language acquired by everyone ever since his birth. A learner encounters mother tongue influence while learning or speaking a foreign language or target language. Mother tongue influence is something that affects a personâ€™s thought process in a sense that he thinks in mother tongue and expresses in English or a second language. People use incorrect pronunciation of words while communicating in English language as they are influenced by the sound patterns of their mother tongue. A second language learner has an unconscious preference to convey his customs from his first language to the target language. The influence of mother tongue has become a significant region and is generally referred to as â€˜Language Interferenceâ€™. Every language learner comes across this issue. Students, sometimes, use words from their parent language while communicating in English. This paper speaks about the difficulties faced by the learners of the second language and the causes of first language influence. This paper attempts to bring out the ways to avoid the overwhelmed influence of mother tongue and gives some notions to the students to develop their second language skills.Â Â